DIACHRONOUS HISTORIES FOR THE DABIE-SULU OROGEN FROM HIGH-TEMPERATURE GEOCHRONOLOGY - Leech M.L.; Webb L.E.; Yang T.N. (My University, 2006)
New U-Pb sensitive high-resolution ion microprobe (SHRIMP) dating of zircon from the ultrahigh-pressure Sulu terrane, eastern China, records three events in the evolution of the orogen. Peak ultrahigh-pressure and retrograde metamorphism in the Middle to Late Triassic (ca. 230-200 Ma) is recorded in zircon mantles and rims; cathodoluminescence imaging, grain morphology, and U-Th-Pb and rare earth element chemistry cannot distinguish between ultrahigh-pressure and retrograde zircon growth. Comparison of high-temperature thermochronology for the Sulu and Dabie-Hong'an areas suggests that peak ultrahigh-pressure metamorphism in Sulu took place at ca. 230 Ma, postdating Dabie-Hong'an by 10 m.y.; this age disparity has implications for collision-subduction-exhumation models for the entire Qinling- Hong'an-Dabie-Sulu orogen and suggests that Sulu was a separate ultrahigh-pressure slab that was never adjacent to Dabie. Relict zircon cores and mantles preserve protolith ages between 700 and 790 Ma, reflecting the Yangtze craton affinity of the Sulu terrane and supporting other evidence indicating that the suture between the Yangtze and Sino-Korean cratons lies along the Yantai-Qingdao-Wulian fault zone. Late Jurassic to Early Cretaceous ages from a pegmatite vein near the suture probably reflect early melting related to a widespread magmatic event that affected the northern margin of the Dabie-Sulu belt. © 2006 Geological Society of America.
Keywords: EASTERN CHINA; QINLING-HONG'AN-DABIE-SULU OROGEN; TRIASSIC ULTRAHIGH-PRESSURE (UHP) METAMORPHISM; U-PB ZIRCON SHRIMP DATING; YANGTZE CRATON; Cretaceous; Jurassic; Triassic; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская; Mesozoic::Triassic; Мезозой::Триасовая